Analisis Perbandingan Biaya Penyusutan Aset Biologis Tanaman Kelapa Sawit Dengan Metode Garis Lurus Dan Jumlah Unit - fitriani saragih (Jurnal Riset Akuntansi dan Bisnis, 2020)
The purpose of this study is to analyze which method is most appropriate for companies, especially those engaged in plantations and production. This type of research is descriptive type. Based on the problem raised by the researcher, this research is classified as a descriptive study. The results show that the results of the comparison using the unit number method in calculating the depreciation of the biological assets of oil palm plants produce smaller depreciation costs than the straight-line method. The use is more proportional than the actual use of the assets. And there is a higher profit using the number of units method than the straight-line method